Good personality and social well-being: The roles of orientation to happiness - Xiaodan Xu; Yang Liu; Liying Jiao; Yongming Wang; Mengke Yu; Yidie Lai; Yingjun Zhang; Yan Xu (Frontiers in Public Health, 2023)
IntroductionPositive personality traits have been associated with personal well-being in previous research. However, the pathways through which positive personality may affect social well-being remain unclear. The present study hypothesized that the cognitive strategies for achieving well-being (i.e., orientation to happiness) mediate the association between good personality and social well-being in the Chinese culture.MethodsA survey including the Good Personality Questionnaire, Social Well-being Scales, and Orientations to Happiness was administered to 1,503 Chinese secondary school students and adults.ResultsThe results indicated that orientation to meaning mediated the relation between good personality and social well-being, but not orientation to pleasure.DiscussionThis is in line with the normative well-being model and the cognition instrumental model of well-being, which contributes to developing more targeted interventions to promote social well-being in the Chinese cultural.